Hoffman–Lauritzen Analysis of Crystallization of Hydrolyzed Poly(Butylene Succinate-Co-Adipate) - Anna Svarcova; Petr Svoboda (Crystals, 2025)
This study systematically investigates the impact of hydrolytic degradation on the crystallization kinetics and morphology of poly(butylene succinate-co-adipate) (PBSA). Gel Permeation Chromatography (GPC) confirmed extensive chain scission, significantly reducing the polymer’s weight-average molecular weight (Mw from ~103,000 to ~16,000 g/mol) and broadening its polydispersity index (PDI from ~2 to 7 after 64 days). Differential scanning calorimetry (DSC) analysis revealed that hydrolytic degradation dramatically accelerated crystallization rates, reducing crystallization time roughly 10-fold (e.g., from ~3000 s to ~300 s), and crystallinity increased from 34% to 63%. Multiple melting peaks suggested the presence of lamellae with varying thicknesses, consistent with the Gibbs–Thomson equation. Isothermal crystallization kinetics were evaluated using the Avrami equation (with n ≈ 3), reciprocal half-time of crystallization, and a novel inflection point slope method, all confirming accelerated crystallization; for instance, the slope increased from 0.00517 to 0.05203. Polarized optical microscopy (POM) revealed evolving spherulite morphologies, including hexagonal and flower-like dendritic spherulites with diamond-shape ends, while wide-angle X-ray diffraction (WAXD) showed a crystallization range shift to higher temperatures (e.g., from 72–61 °C to 82–71 °C) and a 14% increase in crystallite diameter, aligning with increased melting point and lamellar thickness and overall increased crystallinity.